A method for rehabilitating children with cerebral palsy and cerebrospinal diseases with use of an evolutional robot - Diukenjiev, Yevgeny (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The function determines the material and field forms of synergy, the basic law of bionics. Any movement of a purposeful character is realized in the presence of a multilink biokinematic structure and instantaneous control units (synergies) of this structure. Biomechanical or neurological pathology curtails the constructive processes, observed in children with diseases/damages of the brain. The author described purposeful movements at norm and, on this basis, a synthesized back task in case of pathology (deficit of muscular and controlling activities).